Art or intimacy: assessing a disjunction - Moura, Vítor (2021)
Common to both the Expressionist and the Cognitivist standpoints is the notion according to which art provides one of the closest possible contacts between human beings. This peculiar sense of communion may be described at a purely communicational level and perceived as a way by which we attain a profound awareness of our common humanity – the basis for the “universal communicability of judgments of taste”, following Kant’s formula. But it may also inspire us to adopt a quasi-erotic explanation of aesthetic experience. In fact, to be involved, often for quite some time, with someone who seems to share our perspective on reality and was capable of recreating and making available that perspective to others - through psychological interaction of fictional characters, musical forms in expressive motion, or enlightening visual compositions - happens to be one of the most exciting and valuable parts of our lives, of our social life, and indeed a way of setting aside an eventual feeling of loneliness.